Pengembangan Strategi Bisnis Melalui Business Model Canvas Dan Strategi Pemasaran Cv Sari Bumi Sakti Melalui Website - Muhamad Ibrovic; Yudi Santoso; Nurwati Nurwati (Universitas Budi Luhur, 2022)
One of the promotion and marketing media that is currently developing is the website. The website is used to introduce what products are being sold. The website is also a means of communication between sellers and buyers. CV. Sari Bumi Sakti, which is engaged in producing therapeutic oils, uses offline sales by word of mouth and around the environment, so not many are familiar with therapeutic oils. Another problem is when data storage is still manual by writing sales results in books and staff taking turns so that when printing reports it confuses CV owners and takes a long time. Development of business strategy through the Business Model Canvas and CV Sari Bumi Sakti's marketing strategy through the website. The right solution is to compile a Business Model Canvas (BMC) to analyze each block in the BMC so that the problems and shortcomings of the running system are known that must be met in order to compete in the market. Marketing strategy development that has been carried out using social media as sales media is WhatsApp and Instagram. The purpose of this research is to make it easier for the owner to view sales reports, effective sales and sales targets. For this reason, an e-commerce website is designed that can promote therapeutic oil products and an e-commerce-based sales website that can store sales results and then facilitate online sales so that they achieve targets and print sales reports.